Relationship between Central Corneal Thickness and Intraocular Pressure in Selected Pakistani Population - Nasir Bhatti, Ashraf Daud, Mazhar ul Hassan, Aziz ur Rehman, Munawar Abbas, Umar Fawad (Pakistan Journal of Ophthalmology, 2010)
Purpose: To explore the relationship between central corneal thickness (CCT) and intraocular pressure (IOP) in selected Pakistani population and to formulate recommendations for its application in clinical practice as well as future research. Material and Methods: The study was conducted at Al-Ibrahim Eye Hospital Karachi for six months, on five hundred eyes of 250 adults attending the outpatient. After informed consent, all patients underwent a comprehensive assessment including medical and ophthalmic history and examination. Intraocular pressure (IOP) was measured with Goldmann Applanation Tonometer and CCT with ultrasonic pachymeter. Results: Mean CCT in males was measured as 529.5 ± 33.6 (range 438-619 ?m) and 524.1 ± 33.3 (range 443-623 ?m) in females. Mean IOP in males was 12.75 ± 2.85 (range 8-20 mmHg) and in females 12.98 ± 2.39 (range 8-20 mmHg). There was a statistically significant association between CCT and IOP for normal subjects (Pearson correlation coefficient r=0.136, p=0.022). However, no statistically significant relationship was found between CCT and age (p=0.103). Conclusion: CCT is a significant predictor of IOP. Thin corneas lead to an underestimation and thick corneas, to an overestimation of intraocular pressure. Pakistani population in our study has comparatively thinner corneas as compared to Caucasian and African-American population. However further studies with sufficiently large sample size are needed to validate and to demonstrate its original value.